“Evaluation of Attitude of the Endodontists and General Practitioners towards the Importance of the Glide Path in Endodontic” (Journal of Hama University, 2022)
The glide path is defined as a regular opening from the orifice of the root canal to the apical foramen,and it is considered the most important stage of root canal preparation. The aim of this research is to evaluate the attitude of general dental practitioners and endodontists towards importance of the glide path. The sample size comprised 224 endodontists and GDPs in Syria, the survey comprised  7 questions about attitude and practice towards glide path in endodonticThe results showed (93.58%) of respondents created glide path before mechanical preparation of the root canals with a significantly higher proportion of endodontists (99.05%) compared with that of GDPs (82.75%), and overall (79%) of respondents using stainless steel kFiles for preparing the glide path. (100%) of endodontists consider that glide path Reduces risk of instrument separation. After collecting the responses, data were analyzed using chi-square at the 0.05 level of significance.
Keywords: Root canal Preparation , Glide Path ,Hand Files, Instruments Fracture